2007
DOI: 10.1002/bjs.5815
|View full text |Cite
|
Sign up to set email alerts
|

Late results of skin-sparing mastectomy followed by immediate breast reconstruction

Abstract: SSM followed by IBR was both surgically and oncologically safe, especially for early-stage breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
3
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(42 citation statements)
references
References 32 publications
(62 reference statements)
1
36
3
2
Order By: Relevance
“…The specificity of visual inspection has been reported to be 10 to 30 percent in large series. 16,28,29 In the present series, a mastectomy flap necrosis rate of 27 percent was observed in the direct observation group, despite maintaining a "low-threshold" for excising questionable skin during the study period.…”
Section: Discussioncontrasting
confidence: 53%
“…The specificity of visual inspection has been reported to be 10 to 30 percent in large series. 16,28,29 In the present series, a mastectomy flap necrosis rate of 27 percent was observed in the direct observation group, despite maintaining a "low-threshold" for excising questionable skin during the study period.…”
Section: Discussioncontrasting
confidence: 53%
“…This presents a particular issue in immediate breast reconstruction, in which devices add increased stress to already traumatized tissue [18,25]. Literature rates of mastectomy flap necrosis following immediate reconstruction range from 8.7-22%, largely due to variation in mastectomy technique and definition of the outcome [15,18,[26][27][28]. We found in the current assessment that 135 mastectomy flaps (8.6%) were complicated by a degree of necrosis that necessitated surgical débridement.…”
Section: Discussionmentioning
confidence: 77%
“…After an average follow-up of 49 months, there was found to be no significance difference in LR, regional recurrence or the time interval between treatment and recurrence [60]. In a retrospective study of 207 women undergoing SSM and IBR, with a mean follow-up of 70 months, 5.8% of patients with stage 0-2 disease developed LR, compared to 31% of women with stage 3 breast cancer [61]. After an average follow-up of 51 months, the same authors reported only 4 LRs within the native breast skin of 146 women with stage 0-2 IBC treated with SSM and IBR.…”
Section: Oncological Considerationsmentioning
confidence: 92%